2021
DOI: 10.1590/scielopreprints.2658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identificação E Acompanhamento De Alunos Universitários Com Altas Habilidades/Superdotação

Abstract: Nota-se, atualmente, no cenário brasileiro um aumento no número de projetos de pesquisa e ações de apoio para a inclusão do público alvo da educação especial nos sistemas de ensino regular. No entanto, dentro desse público observa-se uma expressiva carência de pesquisas para a identificação e propostas de programas educacionais adequados aos jovens e adultos com altas habilidades/superdotação, particularmente quando estes já estão inseridos nas universidades. Constata-se que as universidades brasileiras não po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…The articles found using the descriptors "High Abilities / Giftedness and Teaching" and "High Abilities / Giftedness and Education", their authors and years, are shown in table 5. Table 5 -Results and conclusions of articles on the descriptors "High Abilities / Giftedness and Teaching" and "High Abilities / Giftedness and Education", with method, author and year of each article Sources: (WECHSLER and SUAREZ, 2016;CALLEGARI, 2019;CUNHA and RONDINI, 2020;MARTINS, 2020;OLVEIRA et al, 2020;PASIAN, 2020;REIS and CAPELLINI, 2020;OLVEIRA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The articles found using the descriptors "High Abilities / Giftedness and Teaching" and "High Abilities / Giftedness and Education", their authors and years, are shown in table 5. Table 5 -Results and conclusions of articles on the descriptors "High Abilities / Giftedness and Teaching" and "High Abilities / Giftedness and Education", with method, author and year of each article Sources: (WECHSLER and SUAREZ, 2016;CALLEGARI, 2019;CUNHA and RONDINI, 2020;MARTINS, 2020;OLVEIRA et al, 2020;PASIAN, 2020;REIS and CAPELLINI, 2020;OLVEIRA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Gli articoli trovati utilizzando i descrittori "abilità elevate/plusdotazione e insegnamento" e "abilità elevate/plusdotazione e istruzione", i loro autori e anni, sono riportati nella tabella 5. Insegnamento" e "abilità elevate/plusdotazione e Educazione", con metodo, autore e anno di ciascun articolo Fonti: (WECHSLER e SUAREZ, 2016;CALLEGARI, 2019;CUNHA e RONDINI, 2020;MARTINS, 2020;OLVEIRA et al, 2020;PASIAN, 2020;REIS e CAPELLINI, 2020;OLVEIRA et al, 2021). interesse (REMOLI et al, 2020).…”
Section: Risultati E Discussioneunclassified
“…Sources : (FAVERI et HEINZLE, 2019 ;RECH et NEGRINI, 2019 ;MARTINS et al, 2020 ;MENDONÇA et al, 2020 ;STREIECHEN et al, 2020). Sources : (WECHSLER et SUAREZ, 2016 ;CALLEGARI, 2019 ;CUNHA et RONDINI, 2020 ;MARTINS, 2020 ;OLVEIRA et al, 2020 ;PASIAN, 2020 ;REIS et CAPELLINI, 2020 ;OLVEIRA et al, 2021). (ZAGO et RIBEIRO, 2017 ;BRUNO, 2020 ;MONTEIRO et PLÁCIDO, 2020 ;OLIVEIRA et FERRÃO, 2021 ;VOLANTE et al, 2021).…”
Section: Résultats Et Discussionunclassified